Sovereignty, Inc. three inquiries in politics and enjoyment - Mazzarella, William 1969-; Santner, Eric L. 1955-; Schuster, Aaron 1974- (The University of Chicago Press, 2020)
"William Mazzarella, Eric Santner, and Aaron Schuster join forces to analyze the disorienting experience of politics in the Trump era. Drawing from anthropology, media theory, political theory, philosophy, and psychoanalysis, the coauthors show how Trump's compulsive self-branding generates a correspondingly obsessive attention on the part of the public. By retweeting news about Trump, whether in praise or in scorn, the public participates in the manufacturing and reproduction of the Trump brand. This circuit, the coauthors argue, generates a form of pleasure on all sides, even for Trump's detractors, to such an extent that it stultifies, rather than galvanizes, forms of political resistance. The book's provocative claim is that regardless of political affiliation, we all enjoy Trump. Each of the book's extended essays tackles different aspects of this perverse enjoyment, resonating richly with each other in the manner of the unique collaboration that defines TRIOS series volumes"--
Keywords: Geschichte 2017-2020; Politische Psychologie; Autorität; Politische Kultur; USA; Trump, Donald / 1946-; Genet, Jean / 1910-1986 / Balcon; Political culture / United States; Branding (Marketing) / Political aspects / United States; Authority; United States / Politics and government / 2017-; Balcon (Genet, Jean); Political culture; Politics and government; United States; Since 2017; Aufsatzsammlung